2019
DOI: 10.1371/journal.pone.0210547
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and iron: Toward understanding the antibacterial effect of ciclopirox in Escherichia coli

Abstract: New antibiotics are needed against antibiotic-resistant gram-negative bacteria. The repurposed antifungal drug, ciclopirox, equally blocks antibiotic-susceptible or multidrug-resistant Acinetobacter baumannii, Escherichia coli, and Klebsiella pneumoniae clinical isolates, indicating that it is not affected by existing resistance mechanisms. Toward understanding how ciclopirox blocks growth, we screened E. coli mutant strains and found that disruption of genes encoding products involved in galactose salvage, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 94 publications
(174 reference statements)
0
16
0
Order By: Relevance
“…Moreover, EMSA experiments detected direct binding between phosphorylated RcsB and the promoter or Intra-CDS regions of some differently expressed genes including the fepE gene which is located within a cluster of genes responsible for enterobactin synthesis and transport. This fact has suggested that fepE may possess a potential biological role regulating co-ordinately O antigen chain polymerization and iron transport ( 57 ), indeed, alteration of LPS has shown to stimulate enterobactin production ( 63 ). Interestingly, the Rcs system is involved in production of colanic acid capsule, thus, an interrelation between O antigen polymerization in LPS and colanic acid in the stress response is plausible as denotes the fact that bacteria without O antigen in LPS overproduces colanic acid ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EMSA experiments detected direct binding between phosphorylated RcsB and the promoter or Intra-CDS regions of some differently expressed genes including the fepE gene which is located within a cluster of genes responsible for enterobactin synthesis and transport. This fact has suggested that fepE may possess a potential biological role regulating co-ordinately O antigen chain polymerization and iron transport ( 57 ), indeed, alteration of LPS has shown to stimulate enterobactin production ( 63 ). Interestingly, the Rcs system is involved in production of colanic acid capsule, thus, an interrelation between O antigen polymerization in LPS and colanic acid in the stress response is plausible as denotes the fact that bacteria without O antigen in LPS overproduces colanic acid ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ciclopirox is an off-patent, broad-spectrum antifungal agent used, as an olamine salt, in various formulations to treat superficial fungal infections [17]. It has recently been found to have considerable potential to act against both Gram-positive and Gram-negative bacterial pathogens [18,19]. The synthetic fluorinated pyrimidine 5-fluorocytosine is used as an antimycotic drug with the brand name Ancobon.…”
Section: In Vitro Cytotoxic Effect On Ib3-1 Cellsmentioning
confidence: 99%
“…FetA (ybbL), the ATP binding subunit of a putative ABC family iron transporter, was associated with decreased cefotaxime and ciprofloxacin susceptibility (fetA-cefotaxime association by PGLS: beta = 3.487, t 4.814,90 = 4.169, corrected p < 0.05; fetAciprofloxacin association by PGLS: beta = 5.204, t 4.546,90 = 7.285, corrected p < 0.001). It has been previously reported that fetA and fetB, the second component of the iron transport system, play a role in resistance to oxidative stress (Nicolaou et al, 2013) and antibiotics (Conley et al, 2019).…”
Section: Known Metal and Biocide Resistance Genes Predict Some Phenotmentioning
confidence: 99%